Community Perceptions on the Development of Indah Beach Marine Ecotourism Activities in Tanjung Aru Village, Sebatik Timur District, Nunukan Regency, North Kalimantan Province - Ismi Nurfatwa; Qoriah Saleha; Erwiantono Erwiantono (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Understanding community perceptions can help to minimize resistance and, on the other side, can maximize community participation in marine ecotourism management. High community support is the key to successful development of marine ecotourism activities. The purpose of this study was to determine the public's perception of the development of marine ecotourism activities at Indah Beach, Tanjung Aru Village, based on the indicators of the Ministry of Tourism. Primary data was taken in August 2023; research and data collection methods used case studies and purposive sampling techniques with a sample size of 30 respondents. The data were analyzed using descriptive statistical methods and a Likert measurement scale. The results showed that people's perceptions of the development of marine ecotourism activities at Pantai Indah based on five ecotourism principles with a score of 79.76, which is in the range of 51.31 - 80.60 with the criteria